Coastline dynamics of the northern Lower Casamance (Senegal) and southern Gambia littoral from 1968 to 2017. (December 2019) - Thior, Mamadou; Sané, Tidiane; Dièye, El hadj B.; Sy, Oumar; Cissokho, Dramane; Ba, Boubacar Demba; Descroix, Luc
Abstract: Northern Lower Casamance and southern Gambia's beaches, just like those of West Africa, are subject to significant morpho-sedimentary dynamics characterized by coastline mobility. Such mobility, combined with significant variations in different places, is characterized by some globally erosive trend (−1.2–6 m/year, in sandy areas extending from Senegal to Sierra Leone and −1 to −15 m/year from Ivory Coast to Nigeria). The purpose of this article is to analyze the coastline evolution in Lower Casamance and southern Gambia based on a diachronic survey (1968–2017). The reference line used to demonstrate the variation of the coastline is the vegetation boundary. The results obtained are based on the digital processing of geospatial data (aerial photographs, Landsat and Google Earth images). The different variations of the coastline are obtained through the calculation of two indexes considered as the most relevant ones. The first one, the End Point Rate (EPR) index, helped measure the difference between two successive coastlines and the second one, the Linear Regression Rate (LRR) index, allows assessing the ability to estimate the evolution of each segment over the entire period considered. These mobility indexes (EPR and LRR) show some variable dynamics of the coastline, featured by two trends: the first one, under accretion in the 1968–1986 period and the other one, globally erosive during 1986–2017 period. Highlights: Due to the socio-economic and ecological importance of the West African coastline, the highlight in this study are: To reflect on the evolution of the coastline to prevent coastal risks in a context of climate change marked mainly by the elevation sea level. By fact that the littoral of northern Lower Casamance and southern Gambia, which is the subject of this study, has for many years now been faced with the decline of the coastline, And then the consequences of which remain significant both environmentally and socioeconomically